Importance of clinical and cytological factors for prediction of efficacy of treatment in persistent corneal epithelial defects and ulcers from different causes (Ukrainian Journal of Ophthalmology, 2026)
Background: Characteristics of persistent corneal epithelial defects (PCEDs) of neurotrophic origin are a long clinical course and abnormal epithelial regeneration; additionally, patients often have complications such as stromal thinning and corneal perforation.Purpose: To investigate the clinical and cytological factors influencing the efficacy of treatment of PCEDs.Materials and Methods: The clinical and cytological factors for prediction of efficacy of treatment in PCEDs of different causes were investigated in 51 patients. We performed general ophthalmological examinations and cytological and immunohistochemical analysis using Millicell filters and antibodies against cytokeratins (CK), “corneal” CK3 and “conjunctival” CK19.Results: The following factors were found to be of significant influence on the achievement of the outcome target (complete re-epithelialization of the corneal surface): size of corneal defect; flat margins of corneal defect; presence of basal cells in cytograms; absence of the cells expressing “corneal” CK3 and presence of the cells expressing “conjunctival” CK19 in immunohistochemistry. Univariant logistic regression was used for the quantitative assessment of the risk of failure to achieve complete re-epithelialization of corneal defects.Conclusion: Using the mathematical model proposed, one can predict the achievement of complete re-epithelialization of the corneal surface with the conservative therapy in 74.5% of the cases with the sensitivity of 72.2% and specificity of 78.8%.
Keywords: persistent corneal epithelial defects; efficacy of treatment; prediction; clinical and cytological factors